2005
DOI: 10.1103/physrevlett.95.211302
|View full text |Cite
|
Sign up to set email alerts
|

Looking for Light Pseudoscalar Bosons in the Binary Pulsar System J0737-3039

Abstract: We present numerical calculations of the photon-light-pseudoscalar-boson conversion in the recently discovered binary pulsar system J0737-3039. Light pseudoscalar bosons (LPBs) oscillate into photons in the presence of strong magnetic fields. In the context of this binary pulsar system, this phenomenon attenuates the light beam emitted by one of the pulsars, when the light ray goes through the magnetosphere of the companion pulsar. We show that such an effect is observable in the gamma-ray band since the binar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 21 publications
0
38
1
Order By: Relevance
“…Experiments along the same lines as described for fourwave mixing above can also be used for a large number of other, non-QED tests, such as axion search [41,48,49]. Thus, progress of low-energy QED experiments could also prove to be useful for, e.g.…”
Section: Photon-photon Scatteringmentioning
confidence: 99%
“…Experiments along the same lines as described for fourwave mixing above can also be used for a large number of other, non-QED tests, such as axion search [41,48,49]. Thus, progress of low-energy QED experiments could also prove to be useful for, e.g.…”
Section: Photon-photon Scatteringmentioning
confidence: 99%
“…Indeed, we will shown that photon-LPB conversion in such a system gives rise to a characteristic attenuation pattern of the light beam emitted by one of the pulsars when it goes through the magnetosphere of the companion. For the values of m and M determined by PVLAS, the production of LPBs turns out to be substantial, so that the resulting attenuation of the beam intensity can become observable in the γ-ray band with the upcoming GLAST mission [14].…”
Section: Many Realistic Extensions Of the Standardmentioning
confidence: 99%
“…One example is "shining light through the Sun" where a high-energy photon source would become visible through the Sun by photon-ALP conversion in the solar magnetic field on the far side of the Sun, and their regeneration on our side [25]. Another example is the double pulsar J0737-3039, where gamma rays emitted by one pulsar periodically pass through the magnetosphere of the other on their way to us [26].…”
Section: Introductionmentioning
confidence: 99%